SMOKING CONTROL ADVOCACY RESOURCE CENTER (SCARC) INFORMATION ALERT SENAGE BANS SMOKING ON ALL DOMESTIC FLIGHTS (Tufts Archival Research Center, 2007)
Information alert from the Smoking Control Resource Center surrounding the Conference Committee reconciliation of the House and Senate airplane smoking ban legislation. Cites the health risks of smoke on airplanes, as well as importance of flight attendant lobbying. Presents industry arguments and responses to them, including ethical and health issues. Lists the members of conference committee.